Nutritional Considerations in Pediatric Pancreatitis: A Position Paper from the NASPGHAN Pancreas Committee and ESPGHAN Cystic Fibrosis/ Pancreas Working Group - Abu-El-Haija, Maisam (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Wide variations exist in how physicians manage the nutritional aspects of children affected by acute pancreatitis (AP), acute recurrent pancreatitis (ARP) and chronic (CP) pancreatitis. Better consensus for optimal management is needed. METHODS: This consensus statement on nutrition in pediatric pancreatic diseases was developed through a joint ESPGHAN-NASPGHAN working group that performed an evidence-based search of the literature on nutrition in AP, ARP, and CP with a focus on pediatrics. The literature was summarized, quality of evidence reviewed, and expert recommendations developed. The authorship met to discuss the evidence and statements. Voting on recommendations occurred over two rounds based on feedback. A consensus of at least 75% was required to approve a recommendation. Areas requiring further research were identified. RESULTS AND DISCUSSION: The literature on nutrition in pediatric pancreatitis is limited. Children with mild AP benefit from starting an early nutritional regimen in the course of the attack. Early nutrition should be attempted in severe AP when possible; enteral nutrition is preferred over parenteral nutrition. Children with ARP are likely to tolerate and benefit from a regular diet. Children with CP need ongoing assessment for growth and nutritional deficiencies, exocrine and endocrine insufficiencies. CONCLUSION: This document presents the first authoritative recommendations on nutritional considerations in pediatric pancreatitis. Future research should address the gaps in knowledge particularly relating to optimal nutrition for AP in children, role of diet or dietary supplements on recurrent attacks of pancreatitis and pain episodes, monitoring practices to detect early growth and nutritional deficiencies in CP and identifying risk factors that predispose children to these deficiencies.